Socioeconomic factors contributing to exclusion of women from maternal health benefit in Abuja, Nigeria - Tajudeen O. Oyewale; Thandisizwe R. Mavundla (Curationis, 2015)
Background: An understanding of the predictive effect of socioeconomic characteristics (SECs) of women on maternal healthcare service utilisation is essential in order to maximise maternal health benefits and outcomes for the newborn.